Do Spin‐offs Expropriate Wealth from Bondholders? - Maxwell, William F.; Rao, Ramesh P. (Journal of Finance, 2003)
Abstract A wealth transfer from bondholders to stockholders is one of several hypotheses used to explain stockholder gains on the announcement of a spin‐off. However, previous empirical research has not found systematic evidence supporting the wealth expropriation hypothesis. Using a larger sample with comprehensive bond data, we find evidence consistent with wealth expropriation. Bondholders, on average, suffer a significant negative abnormal return during the month of the spin‐off announcement. However, even accounting for the loss to the bondholders, the aggregate value of the publicly traded debt and equity increases on a spin‐off announcement, suggesting that the wealth expropriation hypothesis is not a complete explanation of the stockholder gains. In explaining the magnitude of the losses to bondholders, we find they are a function of the loss in collateral in the spun‐off subsidiary and the level of financial risk of the parent firm. Consistent with a loss to bondholders, firms are more likely to have their credit rating downgraded than upgraded after a spin‐off. Additionally, consistent with the wealth transfer hypothesis, losses to bondholders tend to be more severe, the larger the gains to shareholders.